Dinamic of blood pluripotential stem cell formation processes - Švitra, Donatas; Retkutė, Renata (Lietuvos matematikos rinkinys, 1998)
It has been suspected that periodical haematological deases arise because of abnormalities in the feedback mechanism that regulate blood cell number. It is generally believed that there exist the self maintaiting pluripotential stem cell population (PPSC) capable of producing committed stem cells specialised for the erithroid, myleoid or thromboid cell lines. The production of PPSC is regulated by two types of feedback mechanisms: (1) long range humoral mechanisms; (2) local environmental mechanisms. The property of these feedback mechanisms is the presence of time delays which arise, for example, because of finite cell maturation time. With the help of difference-differential equations the processes of the PPSC production are modeled. The models, which use logistic and Mono lows are linear analised and simulated by computer.